The Influence of Mental Accounting and Financial Behavior on Financial Satisfaction - Fatra Istisqa; Novira Sartika (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The rapid development of financial technology accompanied by consumer behavior has increased the financial literacy gap despite the high level of inclusion in Indonesia, triggering an analysis of cognitive and behavioral factors that influence financial satisfaction. This study aims to examine the influence of Mental Accounting and Financial Behavior on Financial Satisfaction among lecturers on Bengkalis Island. Using a quantitative explanatory approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), the population included all active lecturers with a sample of 207 respondents through convenience sampling. Data were collected via an online Likert-scale questionnaire (26 indicators) and analyzed using SmartPLS 4 through outer-inner model evaluation and bootstrapping. The results showed that Mental Accounting (β=0.137, t=2.001, p=0.045) and Financial Behavior (β=0.182, t=2.824, p=0.005) significantly influenced Financial Satisfaction (R²=0.054). The conclusion states that structured financial grouping and disciplined spending habits improve lecturers' financial well-being, suggesting the integration of financial literacy training into professional development programs.